Pengaruh Asupan Asam Folat Terhadap Kejadian Preeklamsi - Lazulfa Inda Lestari (Jurnal Ilmiah Kesehatan Sandi Husada, 2019)
Preeclampsia is one of the three highest factors in the death of a pregnant woman. WHO data states that 585,000 women die annually during pregnancy or childbirth and more than half (58.1%) are caused by preeclampsia and eclampsia. There is a triad of symptoms of preeclampsia namely, proteinuria, edema, and hypertension. Although the cause of preeclampsia is still unknown, the initial stage of pathogenesis begins with an abnormal placenta due to nutrition. One nutrient that plays a role is folic acid. In pregnant women who experience preeclampsia, their folic acid levels are very low and their homocysteine ​​is very high. The recommended intake of folic acid for pregnant and lactating women, is 0.4 mg / day due to folic acid deficiency resulting in preeclampsia suffering from maternal hypertension, proteinuria, kidney damage, and increased fetal death. Folic acid can be found in fresh fruit, yeast, liver, green leaves, and mushrooms. Folic acid acts as a metal donor in the remetilation reaction of homocysteine ​​metabolism. If folic acid deficiency occurs, there will be no change in homocysteine ​​to methionine which ends in hyperhomocysteinemia